Is nelfinavir exposure associated with cancer incidence in HIV-positive individuals?. (19th June 2016) - Boettiger, David C.; Sabin, Caroline A.; Grulich, Andrew; Ryom, Lene; Bonnet, Fabrice; Reiss, Peter; Monforte, Antonella d'arminio; Kirk, Ole; Phillips, Andrew; Bower, Mark; Fätkenheuer, Gerd; Lundgren, Jens D.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Nelfinavir exhibits potent anticancer properties against a range of tumours. However, in 2006/2007, nelfinavir supplies were accidently contaminated with a carcinogen. This analysis investigated the association between nelfinavir use and cancer risk in HIV-positive persons. Design: Observational cohort study. Methods: D:A:D study data was analysed using Poisson regression models to examine associations between cancer incidence and cumulative nelfinavir exposure, current nelfinavir exposure, and exposure to nelfinavir between 1 July 2006–30 June 2007. Results: A total of 42 006 individuals (50% white, 73% male) contributed 303 005 person-years of follow-up between 1 January 2004 and 1 February 2014. At study enrolment, median age was 40 [interquartile range (IQR) 33–46] years and 8305 individuals had a history of nelfinavir use [median duration 1.7 (IQR 0.7–3.4) years]. During follow-up, nelfinavir was used by 2476 individuals for a median of 1.7 (IQR 0.7–3.8) years; 1063 were exposed to nelfinavir between 1 July 2006 and 30 June 2007. Overall, 2279 cancers were diagnosed at a rate of 0.75 [95% confidence interval (95% CI) 0.72–0.78] per 100 person-years. Neither greater cumulative exposure to nelfinavir [adjusted risk ratio (aRR) 0.93 for every additional 5 years, 95% CI 0.82–1.06, P  = 0.26] nor current use of nelfinavir (aRR 0.98 vs other protease inhibitor use, 95% CI 0.68–1.41, P  = 0.92) were associated with cancer risk. The adjusted risk of cancer for participants exposed to nelfinavir between 1 July 2006 and 30 June 2007 compared to those receiving other treatment over this period was 1.07 (95% CI 0.78–1.46, P  = 0.68). Conclusion: Nelfinavir use was not associated with a lower cancer incidence than other protease inhibitor regimens. As of February 2014, exposure to the 2006/2007 contamination of nelfinavir does not appear to be associated with increased cancer incidence.